Dissecting Pulmonary Large-Cell Carcinoma by Targeted Next Generation Sequencing of Several Cancer Genes Pushes Genotypic–Phenotypic Correlations to Emerge. Issue 11 (November 2015) - Pelosi, Giuseppe; Fabbri, Alessandra; Papotti, Mauro; Rossi, Giulio; Cavazza, Alberto; Righi, Luisella; Tamborini, Elena; Perrone, Federica; Settanni, Giulio; Busico, Adele; Testi, Maria Adele; Maisonneuve, Patrick; et al.
Abstract : Introduction: Little is known about genotypic and phenotypic correlations in undifferentiated large-cell carcinoma (LCC) of the lung. Methods: Thirty LCC were dissected by unsupervised targeted next generation sequencing analysis for 50 cancer-associated oncogenes and tumor suppressor genes. Cell differentiation lineages were unveiled by using thyroid transcription factor-1 (TTF1) for adenocarcinoma (ADC) and p40 for squamous cell carcinoma (SQC), dichotomizing immunohistochemistry (IHC) results for TTF1 as negative or positive (whatever its extent) and for p40 as negative, positive, or focal (if <10% of reactive tumor cells). Results: Three LCC were wild type (all TTF1+/p40−), whereas the remaining 27 (90%) tumors had at least one gene mutation. Twenty-four cases featuring TTF1+/p40−, TTF1+/p40±, TTF1−/p40±, or TTF1−/p40− phenotypes comprised ATM, BRAF, CDKN2A, EGFR, ERBB4, FBXW7, FLT3, KRAS, NRAS, PIK3CA, PTPN11, RET, SMAD4, SMO, STK11, or TP53 mutations in keeping with ADC lineage, whereas three tumors showing TTF1−/p40+ phenotype harbored TP53 only and no ADC-related mutations in keeping with SQC lineage. Single, double, triple, quadruple, and quintuple mutations occurred in 16, 6, 2, 2, and 1 patient, respectively. The occurrence of three mutations or more but not any immunohistochemistry categorization predicted shorter overall survival (OS, p = 0.001) and disease-free survival (DFS, p = 0.007), independent of age, sex, and tumor stage. Conclusions: Albeit preliminary also because of the relatively small number of LCC under evaluation, this targeted next generation sequencing study, however, revealed gene mutation heterogeneity in LCC with some genotypic–phenotypic correlations. Negativity or focal occurrence of p40 made SQC diagnosis unlikely on molecular grounds, but suggested ADC confirming validity of the axiom "no p40, no squamous."